2020
DOI: 10.1111/jfbc.13221
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effect of imidacloprid insecticide: The ameliorative effect of pre and post exposure to olive oil

Abstract: Imidacloprid, a systemic chloro–nicotinyl insecticide belong to neonicotinoid insecticides. In this study 120 rats were divided into four groups, the first group used as a control group, the second group was administered imidacloprid at a dose of 22.5 mg/kg b.w. for 4, 8, and 12 weeks. The third group was treated with olive oil (OLO) in a dose of 10 ml/kg body weight for 2 weeks before the oral dose of imidacloprid for 4, 8, and 12 weeks. The fourth group was given OLO in a dose of 10 ml/kg b.w. for 2 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…27 Therefore, we used the neuroblastoma cell lines for the toxic effects of imidacloprid and thiamethoxam. Some studies stated that neonicotinoids might have genotoxic effects; 8,[38][39][40][41][42][43][44][45][46][47] however their effects on molecular and especially epigenetic mechanisms defining the regulation of such toxic effects remains to be elucidated. In our previous study we observed cell viability data that showed that 50% of inhibitory concentration values of imidacloprid and thiamethoxam were in 3.69 and 1.33 mM in SHSY-5Y cells for 24 h. 29 We also demonstrated imidacloprid and thiamethoxam caused DNA damage by comet assay only at 500 µM after 24 h and 48 h exposure in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 Therefore, we used the neuroblastoma cell lines for the toxic effects of imidacloprid and thiamethoxam. Some studies stated that neonicotinoids might have genotoxic effects; 8,[38][39][40][41][42][43][44][45][46][47] however their effects on molecular and especially epigenetic mechanisms defining the regulation of such toxic effects remains to be elucidated. In our previous study we observed cell viability data that showed that 50% of inhibitory concentration values of imidacloprid and thiamethoxam were in 3.69 and 1.33 mM in SHSY-5Y cells for 24 h. 29 We also demonstrated imidacloprid and thiamethoxam caused DNA damage by comet assay only at 500 µM after 24 h and 48 h exposure in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%